2008
DOI: 10.1002/cjoc.200890405
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification by Compositionally Modulated Multilayered Zn‐Fe Alloy Coatings

Abstract: Compositionally modulated multilayered alloy (CMMA) coatings of Zn-Fe were developed from acid chloride baths by single bath technique. The production and properties of CMMA Zn-Fe coatings were tailored as a function of switching cathode current densities (SCCD's) and thickness of individual layers. Corrosion rates (CR) were measured by electrochemical methods. Corrosion resistances were found to vary with SCCD's and the number of sub layers in the deposit. SCCD's were optimized for production of Zn-Fe CMMA el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In 2008, Thangaraj et al reported the preparation of similar coatings with a comparable total thickness in 2008 in which the coatings were made up from <600 layers, using a layer thicknesses as low as 10 nm. These nanoscale zinc rich (Zn-Fe)/iron rich (Zn-Fe) multilayers were reported to have mean corrosion rates as low as 0.025 mm y −1 ) in 5% NaCl at 25 o C [53].…”
Section: Zn-m Multilayers For Corrosion Protection Of Steelmentioning
confidence: 99%
“…In 2008, Thangaraj et al reported the preparation of similar coatings with a comparable total thickness in 2008 in which the coatings were made up from <600 layers, using a layer thicknesses as low as 10 nm. These nanoscale zinc rich (Zn-Fe)/iron rich (Zn-Fe) multilayers were reported to have mean corrosion rates as low as 0.025 mm y −1 ) in 5% NaCl at 25 o C [53].…”
Section: Zn-m Multilayers For Corrosion Protection Of Steelmentioning
confidence: 99%
“…Kirilova et al [18][19][20] reported CMA coatings of Zn-Co from SBT. Recently, Thangaraj et al [21] optimized a chloride bath for the production of Zn-Fe CMA coatings over mild steel, and showed that coating were found to have *45 times better corrosion stability than monolithic Zn-Fe coatings of same thickness. Though improvement in corrosion resistance of Zn-Ni CMA electrodeposits, were widely reported, very little was done with regard to optimization of the deposition condition, using SBT to achieve the peak performance against corrosion.…”
Section: Introductionmentioning
confidence: 98%
“…In this direction, Thangaraj et al (2008) have recently studied the corrosion behavior CMMA Zn-Fe alloy through SBT, using glycine as additive. The corrosion rates were calculated from Tafel's extrapolation method, supported by EIS study.…”
Section: Introductionmentioning
confidence: 99%